Interindividual registration and dose mapping for voxelwise population analysis of rectal toxicity in prostate cancer radiotherapy. Issue 6 (9th May 2016) - Dréan, Gaël; Acosta, Oscar; Lafond, Caroline; Simon, Antoine; de Crevoisier, Renaud; Haigron, Pascal
Abstract : Purpose: Recent studies revealed a trend toward voxelwise population analysis in order to understand the local dose/toxicity relationships in prostate cancer radiotherapy. Such approaches require, however, an accurate interindividual mapping of the anatomies and 3D dose distributions toward a common coordinate system. This step is challenging due to the high interindividual variability. In this paper, the authors propose a method designed for interindividual nonrigid registration of the rectum and dose mapping for population analysis. Methods: The method is based on the computation of a normalized structural description of the rectum using a Laplacian‐based model. This description takes advantage of the tubular structure of the rectum and its centerline to be embedded in a nonrigid registration‐based scheme. The performances of the method were evaluated on 30 individuals treated for prostate cancer in a leave‐one‐out cross validation. Results: Performance was measured using classical metrics (Dice score and Hausdorff distance), along with new metrics devised to better assess dose mapping in relation with structural deformation (dose‐organ overlap). Considering these scores, the proposed method outperforms intensity‐based and distance maps‐based registration methods. Conclusions: The proposed method allows for accurately mapping interindividual 3D dose distributions toward a single anatomical template, opening the way for further voxelwise statistical analysis.